2004
DOI: 10.1095/biolreprod.103.026302
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Regulated Genes in the Murine Epididymis1

Abstract: The epididymis is an androgen-responsive tissue where spermatozoa mature and gain motility. The three major regions of the epididymis, caput, corpus, and cauda, are known to have different functions and exhibit varied gene expression. Specific genes within the different regions of the epididymis have been identified to be under the influence of androgens. The goal of this study was to begin to elucidate the profile of androgen-responsive genes that may be important for sperm maturation using the Affymetrix MGU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 42 publications
2
45
0
1
Order By: Relevance
“…Expression of proteins secreted from epididymal epithelium are often regulated by testicular factors or androgen (Chauvin and Griswold, 2004;Johnston et al, 2005). We analyzed the expression of BPI in caput and caudal epididymides of rats that had been bilaterally castrated and reared for 7 days.…”
Section: Effects Of Castration On the Expression Of Bpimentioning
confidence: 99%
“…Expression of proteins secreted from epididymal epithelium are often regulated by testicular factors or androgen (Chauvin and Griswold, 2004;Johnston et al, 2005). We analyzed the expression of BPI in caput and caudal epididymides of rats that had been bilaterally castrated and reared for 7 days.…”
Section: Effects Of Castration On the Expression Of Bpimentioning
confidence: 99%
“…Many genes show androgen-dependent expression patterns as revealed by individual studies and the comprehensive profiling of gene expression changes before and after orchidectomy in the rat [13][14][15][16]. In the mouse, by castration and dihydrotestosterone (DHT) replacement, the androgen-responsive genes including up-or down-regulated by DHT were identified [17]. Previous studies reported changes in gene expression during epididymal development and aging including 5a-reductases, E-cadherin, occludin, and ZO-1 which decline during aging [18].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we detected four epididymal androgen-responsive genes, namely Adam7, Fkbp5, Gldc, and Gpx5 (36,37). No miR-29a-and miR-29b-binding sites on the 3Ј-UTR of these four genes were predicted using the on-line software miRWalk, indicating that they should not be direct targets of miR-29a and miR-29b.…”
Section: Androgen Negatively Regulates Mir-29a Expression In Epi-mentioning
confidence: 96%